Effect of Co, Cu, and Zn on FeAlK catalysts in CO2 hydrogenation to C5+ hydrocarbons. Issue 3 (4th January 2022) - Nasriddinov, Khasan; Min, Ji-Eun; Park, Hae-Gu; Han, Seung Ju; Chen, Jingyu; Jun, Ki-Won; Kim, Seok Ki
Abstract : Comprehensive comparisons of Co, Cu, and Zn effects on the performance of Fe catalysts in CO2 hydrogenation to liquid hydrocarbons. Abstract : Direct CO2 hydrogenation to long-chain hydrocarbons can mitigate global warming by extensively replacing fossil fuels. However, designing a suitable catalyst with high catalytic activity and C5+ hydrocarbon selectivity continues to be a crucial challenge. Herein, we investigate the promotional effect of Co, Cu, and Zn (Me, hereinafter) addition to FeAlK, which is used in long-chain hydrocarbon production from CO2 hydrogenation. Generally, the addition of Me facilitated ferrite and carbide formation, thereby increasing CO2 conversion and C5+ selectivity. However, no strong correlation was observed between phase composition and catalyst performance by inter-catalyst comparisons. Despite the addition of a small amount of Zn, the CO2 conversion and C5+ selectivity increased significantly. XRD, CO2 -TPD, and XPS results suggest that the easy formation of a Zn ferrite alloy and the resulting large number of basic sites are responsible for the superior performance of Zn–FeAlK in CO2 hydrogenation to long-chain hydrocarbon production.